A novel strategy to identify the critical conditions for growth-induced instabilities - Javili, Ali; Steinmann, Paul; Kuhl, Ellen (Journal of the Mechanical Behavior of Biomedical Materials, 2014)
Geometric instabilities in living structures can be critical for healthy biological function, and abnormal buckling, folding, or wrinkling patterns are often important indicators of disease. Mathematical models typically attribute these instabilities to differential growth, and characterize them using the concept of fictitious configurations. This kinematic approach toward growth-induced instabilities is based on the multiplicative decomposition of the total deformation gradient into a reversible elastic part and an irreversible growth part. While this generic concept is generally accepted and well established today, the critical conditions for the formation of growth-induced instabilities remain elusive and poorly understood. Here we propose a novel strategy for the stability analysis of growing structures motivated by the idea of replacing growth by prestress. Conceptually speaking, we kinematically map the stress-free grown configuration onto a prestressed initial configuration. This allows us to adopt a classical infinitesimal stability analysis to identify critical material parameter ranges beyond which growth-induced instabilities may occur. We illustrate the proposed concept by a series of numerical examples using the finite element method. Understanding the critical conditions for growth-induced instabilities may have immediate applications in plastic and reconstructive surgery, asthma, obstructive sleep apnoea, and brain development. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-TM.anovel
Keywords: Growth; Instabilities; Morphogenesis; Prestress; Residual stress; Stability analysis